Social cost-benefit analysis of air pollution control measures - Advancing environmental-economic assessment methods to evaluate industrial point emission sources - van der Kamp, Jonathan (KIT Scientific Publishing, 2017)
This book enhances economic methods for social cost-benefit analysis of air pollution control measures at point emission sources. A new and highly resolved health damage cost assessment framework is developed and applied, notably in order to evaluate the influence of site-dependent and generic methodological choices. Several of these are shown to have a major impact on resulting health damage costs with important implications for decision-making.